An Evaluation of Solar Energy in Taman Air Manis, Sabak Bernam - Abu Mansor, Nuramanina Zahraa; Abdul Wahid, Abdul Zaki; Awang, Mariah (Progress in Engineering Application and Technology, 2023)
In this era of globalization, the increase in the adoption of new technologies and new innovations that can bring the country forward from other countries. It is an advantage when the existing power source can be replaced using technology especially the power source used in everyday life. Among the examples of technology that we use more today is solar technology that is increasingly used in residential areas and large buildings around the world. Thus, in this study to analyse the public awareness regarding solar energy Taman Air Manis, Sabak Bernam, Selangor and to identify the public perception towards solar energy. The high cost is one of the factors in inhibiting the use of solar energy among the community especially in the low-income group. The questionnaire is made using a google form and distributed to the residents of Taman Air Manis, Sabak Bernam, Selangor. This study was carried out by making a google form and distributed to experts in the solar field because they have experience in the manufacture and installation of solar panels for a house. The analysis was done using the questionnaire form instrument to 247 respondents. The data was analyses using the Statistical Package for Social Sciences (SPSS) version 26. Solar energy can bring more benefits to the people . Solar energy has the least negative impact on the environment of any other energy source and reduces greenhouse gas emissions. Residents can also be exposed to solar energy knowledge. Based on the analysis of the data, the population agreed with this study to analyze the public’s awareness of solar energy and the population neither agree nor disagree about perception towards solar energy.